Faktor-Faktor Kualitas Hidup Pasien Dengan Penyakit Paru Obstruktif Kronik - Tri Antika Rizki Kusuma Putri; Dian Anggraini; Dita Merdekawati (Jurnal Keperawatan BSI, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is lung damage caused by the exposure of certain irritant particles like nicotine from smoking over long period of time. COPD’s clients often seek for health care service from respiratory problems such as persistent or progressive dispneu as a result from exacerbation. Confidence to take care of their health is a prior thing to help clients maintain their condition and it can lead an improvement on physical, psychological, and social aspects on their life. Objectives: This research aimed to identified the dominant factors on quality of life among COPD’s client’s. Method: The method used in this research was quantitative method with cross sectional approach with 71 COPD clients as samples. The COPD Self-Efficacy Scale with 30 questions and WHOQOL-BREF with 25 questions were applied. All data were analysed using linier regression. The result from this study showed a gender, activity, and education level were the dominants factors of quality of life among COPD client’s. Conclusion: The quality of life can be improved by having a good activity in COPD’s clients. Nurse and other healthcare professional need to design an intervention to improve the activity of clients and avoid of exacerbation condition especially in rehabilitation phase.